2007
DOI: 10.1038/sj.emboj.7601659
|View full text |Cite
|
Sign up to set email alerts
|

Selective role for RGS12 as a Ras/Raf/MEK scaffold in nerve growth factor-mediated differentiation

Abstract: Regulator of G-protein signaling (RGS) proteins accelerate GTP hydrolysis by heterotrimeric G-protein a subunits and thus inhibit signaling by many G protein-coupled receptors. Several RGS proteins have a multidomain architecture that adds further complexity to their roles in cell signaling in addition to their GTPase-accelerating activity. RGS12 contains a tandem repeat of Ras-binding domains but, to date, the role of this protein in Ras-mediated signal transduction has not been reported. Here, we show that R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
91
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 74 publications
9
91
1
Order By: Relevance
“…In the case of the MAPK pathway, it has been reported that scaffold proteins promote the formation of complexes containing receptors (30,50). Here we showed that Freud-1/Aki1 interacts with PDK1 and Akt and regulates Akt activation upon EGF signaling by functioning as a scaffold.…”
Section: Identification Of the Domains Responsible For Interactions Ofmentioning
confidence: 61%
See 1 more Smart Citation
“…In the case of the MAPK pathway, it has been reported that scaffold proteins promote the formation of complexes containing receptors (30,50). Here we showed that Freud-1/Aki1 interacts with PDK1 and Akt and regulates Akt activation upon EGF signaling by functioning as a scaffold.…”
Section: Identification Of the Domains Responsible For Interactions Ofmentioning
confidence: 61%
“…As the scaffold, Freud-1/Aki1 specifically and effectively activates Akt among several PDK1 substrates. Moreover, in the case of the MAPK pathway, it has been reported that scaffold proteins form complexes with receptors (30,50). An interesting observation is that increased interactions of Freud-1/Aki1 with EGFR and Akt occurred after EGF stimulation, whereas interactions of Freud-1/Aki1 with IGF-1R and Akt were not detected after IGF-1 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The R7 subfamily of RGS6, -7, -9, and -11 form dimers with G␤5 (9) via a G␥-like domain N-terminal to their RGS domain. The R12 subfamily constitutes RGS10, -12, and -14, with the latter two sharing additional domains reflecting unique roles as Ras/Raf/ MAPK scaffolds (10). The other four subfamilies are signaling regulators that have since become associated with the RGS protein superfamily (5,11) upon discovery of more distantly related RGS domains within them (i.e., Axin, Axil; RhoGEFs p115-RhoGEF, LARG, and PDZ-RhoGEF; the sorting nexins SNX13, -14, and -25; the GPCR kinases GRK1-7).…”
mentioning
confidence: 99%
“…These results were in agreement with the previous report that RGS12 serves as a Ras/Raf/MEK scaffold to accelerate ERK1/2 activation during neuronal differentiation. 21 Furthermore, the requirement of the MEK1/2-ERK1/2 signaling for RGS12-exacerbated cardiac hypertrophy and heart failure was validated by the rescue experiments using the MEK1/2-specific inhibitor U0126. On one hand, activated ERK1/2 translocate to the nucleus and thus phosphorylate transcription factors, such as Elk-1 and GATA4, resulting in the hypertrophic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…18 Huang et al 20 reported that RGS12 inactivates phosphorylated Gαi to ameliorate the inhibition of cAMP formation and thus facilitates muscle relaxation. In addition, Willard et al 21 found that RGS12 serves as a scaffold and organizes Abstract-Cardiac hypertrophy is a major predictor of heart failure and is regulated by diverse signaling pathways. As a typical multi-domain member of the regulator of G-protein signaling (RGS) family, RGS12 plays a regulatory role in various signaling pathways.…”
mentioning
confidence: 99%